Catalytic performance of imidazolium based ILs in the reaction of 1, 2-epoxyoctane and carbon dioxide: Kinetic study. (June 2016) - Jaiswal, Pooja; Varma, Mahesh N.
Highlights: Kinetics of cycloaddition reaction catalyzed by ionic liquids evaluated. Potential of ionic liquids utilized under supercritical CO2 . Catalytic activity enhances with increasing alkyl chain length of cation. Tetrafluoroborate anion has better catalytic activity compared to bromide anion. 1-hexyl-3-methylimidazolium tetrafluoroborate has lowest activation energy. Abstract: In the present study, the synthesis of cyclic carbonate by cycloaddition reaction of CO2 and epoxide catalyzed by imidazolium salts ionic liquids, was carried out under supercritical condition of CO2 . In order to elucidate an effect of imidazolium based ILs on reaction kinetics, the cycloaddition reaction with various ILs of different cations and anions, ranging from C2 to C6 alkyl chain, and BF4 − and Br −, respectively, were studied at various temperature (90–130 °C). Based on batch experiment results it was observed that the ILs with longer alkyl chain cation and BF4 − anion, i.e., 1-hexyl-3-methylimidazolium tetrafluoroborate, showed a comparatively maximum catalytic activity. Furthermore, the pseudo first order reaction kinetics was observed predominant during cyclic carbonate synthesis under supercritical condition. The kinetic analysis of cycloaddition reaction, in the present study, confirms the maximum conversion efficiency and minimum activation energy (37 kJ/mol) was associated with HmimBF4 and therefore, renders HmimBF4 IL a potential catalyst for cyclic carbonate synthesis under supercritical condition.